Sociodemographic disparities in everyday discrimination among a national sample of adults in the United States, 2023 - Delvon T. Mattingly; Osayande Agbonlahor; Joy L. Hart (Preventive Medicine Reports)
Objective: Discrimination is a social determinant contributing to health inequities in the United States (US). This study investigated the prevalence of, and sociodemographic disparities in, perceived everyday discrimination among a national sample of US adults. Methods: We used data from the 2023 National Health Interview Survey (n = 27,538) and estimated the prevalence of three perceived everyday discrimination outcomes (1) any discrimination, (2) unique components of the discrimination experience, and (3) the Everyday Discrimination Scale (EDS) (range: 0–20) overall and by age, sex assigned at birth, race and ethnicity, sexual orientation, educational attainment, income-to-poverty ratio, and urban-rural status. Results: Over half of US adults experienced any discrimination (55.8 %), and the most common form of perceived discrimination was being treated with less respect (45.2 %). Adults who were younger (aged 18–44), female, non-Hispanic Black, sexual minority, some college-educated, low income, or urban-living generally reported higher discrimination. For example, among the sample, non-Hispanic Black (vs. non-Hispanic White) (OR: 1.61, 95 % CI: 1.44–1.81) and sexual minority (vs. heterosexual) (OR: 2.48, 95 % CI: 2.12–2.90) adults had the highest odds of any discrimination and EDS scores (β: 1.38 (95 % CI: 1.17–1.59) and β: 1.65 (95 % CI: 1.35–1.94), respectively). The odds of perceived discrimination varied in magnitude by specific experience; for example, sexual minority adults had the highest odds of being threatened or harassed (OR: 2.93, 95 % CI: 2.52–3.42). Conclusions: Perceived everyday discrimination is prevalent and differentially affects adults, especially members of marginalized and underserved populations. Understanding discrimination patterns will benefit public health and medical efforts aimed at mitigating exposure and deleterious health consequences.